Speaking in turns and sequences: Interactional competence as a target construct in testing speaking. (July 2018) - Roever, Carsten; Kasper, Gabriele
In the assessment of speaking, a psycholinguistically based speaking construct has predominated. In this paper, we argue for the integration of the construct of interactional competence (IC) in speaking assessments to broaden the range of defensible inferences from speaking tests. IC emphasizes the co-constructed nature of interaction and enables the rating of L2 users' ability to deploy interactional tools that lead to shared understandings. Recent work on IC shows that levels of development can be distinguished, for example, in the sequential organization of social actions such as requests and refusals. This can in turn inform interactionally specific ratings. Furthermore, an IC perspective allows a fine-grained analysis of interactions between examiners and test takers to detect effects of examiner talk. Apparent misunderstandings or disfluencies by test takers can be examiner-induced with the test taker's response actually demonstrating interactional ability rather than lack of proficiency. We argue that inclusion of IC as a construct in testing speaking opens new perspectives on oral proficiency and enhances the validity of speaking assessments.